Confirmation of Glyphosate-Resistant Horseweed (Conyza canadensis) in Montana Cereal Production and Response to POST Herbicides. (11th September 2017) - Kumar, Vipan; Jha, Prashant; Jhala, Amit J.
Abstract : In recent years, horseweed has become an increasing problem in Montana. To confirm and characterize the level of glyphosate resistance, seeds were collected from putative glyphosate-resistant (GR) horseweed (GR-MT) plants in a wheat–fallow field in McCone County, MT. Known GR (GR-NE) and glyphosate-susceptible (GS-NE) horseweed accessions from Lincoln, NE, were included for comparison in dose–response and shikimate accumulation studies. Whole-plant glyphosate dose–response experiments conducted at the early- (5- to 8-cm diameter) and late- (12- to 15-cm diameter) rosette stages of horseweed indicated that GR-MT accessions had a 2.5- to 4.0-fold level of resistance to glyphosate relative to the GS-NE accession, on the basis of shoot dry weight (GR50 values). The level of resistance was 3.1- to 7.9-fold on the basis of visually assessed injury estimates (I50 values). At the whole-plant level, about 2.1- to 4.5-fold higher shikimate accumulation was observed in the GS-NE accession compared with the GR-MT and GR-NE accessions over a 10-d period after glyphosate was applied at 1, 260 g ae ha −1 . In a separate greenhouse study, all three horseweed accessions were also screened with alternate POST herbicides registered for use in wheat–fallow rotations. The majority of the tested herbicides provided ≥90% injury at the field-use rates for all three horseweed accessions 3 wk after treatment. This is the first published report on the occurrence of GR horseweed in Montana cereal production. Increased awareness and adoption of best management practices, including the use of diversified (based on multiple sites of action) herbicide programs highlighted in this study, would aid in mitigating the further spread of GR horseweed in the cereal production fields of the U.S. Great Plains.